2017
DOI: 10.1002/slct.201702087
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Novel 2‐Phenylthiazole Derivatives for the Treatment of Alzheimer's Disease

Abstract: A new series of 2‐phenylthiazole derivatives were designed, synthesized, characterized and evaluated as potential candidates to treat Alzheimer's disease. Most of these compounds exhibited significant acetylcholinesterase inhibitory activities. Among them, compound ethyl 2‐[4‐(4‐{[2‐(pyrrolidin‐1‐yl)ethyl]amino}butoxy)phenyl]thiazole‐4‐carboxylate (5 b–8) exhibited the best acetylcholinesterase inhibition activity with IC50 values of 4.8 μM. Moreover, the compound ethyl 2‐(4‐{[5‐(cyclohexylamino)pentyl]oxy}phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…[4][5][6] We have previously synthesised a series of 2-phenylthiazole derivatives and found that these derivatives possess AChE-and BuChE-inhibiton activities. 7,8 In this study, three novel 2-phenylthiazole derivatives were synthesised and characterised by NMR and single-crystal X-ray diffraction analysis. The role of intermolecular interactions in these compounds was analysed through single-crystal structure studies.…”
mentioning
confidence: 99%
“…[4][5][6] We have previously synthesised a series of 2-phenylthiazole derivatives and found that these derivatives possess AChE-and BuChE-inhibiton activities. 7,8 In this study, three novel 2-phenylthiazole derivatives were synthesised and characterised by NMR and single-crystal X-ray diffraction analysis. The role of intermolecular interactions in these compounds was analysed through single-crystal structure studies.…”
mentioning
confidence: 99%